An Unusual Cause of Thoracic Pain in a Child - MM, van Berkel; ME, Mérelle; RR, Gorter; MW, Oomen (Archives of Clinical and Medical Case Reports, 2019)
In adults, late presentation of traumatic diaphragmatic hernia is well known. In children it is rarely reported. We report the case of a fourteen-year-old boy that presented on the emergency department of our hospital with progressive pain at the right hemi thorax. Only with a thorough medical history, a relationship between his complaints and a car accident nine years ago could be made. This resulted in the right diagnosis. At first presentation after thoracic and/or abdominal trauma, there must be awareness of the possibility of diaphragmatic rupture, although the prevalence is low. There is a high chance of missing diagnosis by overshadowing complaints and diagnostic difficulties. The hernia can be discovered years after trauma. Management is primarily surgical.